THE ROLE OF WOMEN'S GROUPS EMPOWERMENT IN STRENGTHENING INDEPENDENT MSMES, BUSINESS UNITS “TELOR ASIN, KERIPIK SINGKONG AND KERUPUK OPAK NASI” IN CIBUNGUR VILLAGE, SUKARESMI REGENCY, PANDEGLANG - Harsono, Pramudi; Haerullah, Edi; Maulana, Masdani; Fajri , Ihsan Awalul; Elsabina, Salwa; Simanjuntak, Oktavia Veronika; Sutisna, Nana (International Journal of Engagement and Empowerment (IJE2), 2025)
This community service activity aims to increase the economic capacity of residents by strengthening independent micro, small, and medium enterprises (MSMEs) based on local potential in Cibungur Village. The program, implemented by Bina Bangsa University's Community Service Program (KKM) students in 2025, focused on training and mentoring in producing salted eggs and rice crackers. A participatory approach was used to build community independence in product processing, marketing, and business management. The activity results showed improved community skills in food processing and entrepreneurial spirit, and the formation of an institutionalized village MSME. This activity demonstrates that university involvement through KKM can strengthen local capacity sustainably.